POLA PENYEBARAN SERANGAN RINTISAN KUMBANG AMBROSIA PLATYPUS TREPANATUS PADA DOLOK KAYU RAMIN - Paimin Sukartana; A Martawijaya (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The distribution pattern of the initial attack of ambrosia beetles Platypus trepanatus Chap. (Coleoptera: Platypodidae) on ramin logs (Gonystylus bancanus Kurz.s ) was studied. Six fresh cut test logs, each of about 25 cm in diameter and 50 cm in length, were barked and horizontally kept in a row of 20 cm apart at about 75 cm above the ground on a pair of sleepers. The surface of each log was longitudinally divided into eight equal parts, i.e. two single ones of the top and bottom face and three paired others situated of the upper sides, sides, and lower sides.The result showed that the attacks were not equally scattered over the whole face of the logs. The most violent attack was found on both the upper side parts. The number of tunnels on these parts were significantly different than those on the others. The lighter infested parts were respectively recorded on the side, top, lower sides, and bottom face of the logs. More than 90% of the initial infestations were concentrated on the upper side and side parts, covering 50% of the surface area of a log.